1999
DOI: 10.1007/s007840050070
|View full text |Cite
|
Sign up to set email alerts
|

The tooth-worm: historical aspects of a popular medical belief

Abstract: The concept of a tooth-worm, which according to popular belief, caused caries and periodontitis, has existed in diverse cultures and across the ages. During the Enlightenment, however, the theory of the tooth-worm was assigned by medical doctors almost exclusively to superstition. Even so, the idea that toothache was caused by gnawing worms held on even into this century. There were many different ideas with regard to the appearance of tooth-worms. In England, for instance, it was thought that the tooth-worm l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…The belief that a worm developed in a bad tooth, started to pick upon the tooth structure immediately and then died as soon as it came into contact with air can be traced back to Paracelsus (1493-1541) (Gerabek, 1999).…”
Section: History Of Demineralizationmentioning
confidence: 98%
See 1 more Smart Citation
“…The belief that a worm developed in a bad tooth, started to pick upon the tooth structure immediately and then died as soon as it came into contact with air can be traced back to Paracelsus (1493-1541) (Gerabek, 1999).…”
Section: History Of Demineralizationmentioning
confidence: 98%
“…The legend of the worm is also found in the writings of Homer, as well as the great surgeon of the middle ages, Guy de Chauliac (1300-1368 A.D.), who still espoused the belief that worms caused dental decay. The famous Flemish surgeon Jan Yperman (who died about 1330) claimed to have observed that the moving worms caused suppuration in the teeth (Gerabek, 1999).…”
Section: History Of Demineralizationmentioning
confidence: 99%
“…Very interestingly, and differently from other folk illnesses related to "worms" and described in the medical anthropological literature in Europe, which generally involve other body districts (tooth, hearth, fingers, hair: Grabner, 1963;Gerebek, 1999;Quave and Pieroni, 2005), in Turkey eyes are also thought to be affected by "worms".…”
Section: Aerial Parts Of Sideritis Speciesmentioning
confidence: 92%
“…1 With the 17th century came the age of enlightenment, during which many old beliefs, including the dental worm theory, were questioned. 4 The first person to reject this theory was Pierre Fauchard, who theorized that sugar was most likely responsible for dental caries. For this contribution he is now known as the father of modern dentistry.…”
mentioning
confidence: 98%